Determination of Sustainable Heritage Preservation Zone using Multi-Criteria Analysis in Taiping City - Anis Ismail, Muhammad; Mokhtar, Salbiah; Rusli, Noradila; Najib Husain, Mohd (International Journal of Engineering and Technology, 2018)
Urban sustainable heritage preservation is not just seen as a heritage building only, but also the factors that influence the building that should also be considered so that any changes in any part of the urban will not change the urban fabrics. Therefore, the relationship between heritage buildings with other planning information can be seen in creating integrated area sustainable preservation plan. The aim of this research is to analyze the Geography Information System application in upgrading the existing information together with the urban sustainable heritage preservation information in developing an integrated area sustainable preservation plan. Geography Information System was chosen as tools because of its significant data manipulation, higher efficiency in generate many alternative scenario and accessible to the data. The question is what are the sustainable criteria to selecting of areas heritage preservation? The objective for this study is to produce sustainable criteria in determining the selection of area for action based on the difference information land use and visual quality heritage preservation. The second question in this study which is how to determine the heritage preservation action based on sustainable criteria? The second objective in this study is to design and developing a Geographical Information System database than can be used in the determination analysis heritage preservation area. The third question in this study where are the sustainable area for heritage preservation in Taiping City? the third objective in this study to produce the result analysis of the analyzing pattern and the thematic maps to identify area of action for preservation zone in Taiping City. This study employed the qualitative approach with the application of document analysis as the research design. Data collection was divided into two groups that is primary data and secondary data. Primary data were obtained through interview with several respondents and secondary data were obtained through documents, books, articles, journals and other sources of reading material. The data of heritage building and planning information the basic in the stage of designing the heritage databases for Taiping. The design of the databases considers all needs in area sustainable preservation. There are two type of analysis model designed based on the integrated conservation actions. The first model is about to determination the threat area and need for conservation. The factors that be considered for this analysis consist land use, visual and location factors. While the second model analysis is about the action control for building sustainable preservation that consists of the history, architectural style and building condition to ensure the appropriate history action through the preservation heritage building. The final output for this research is the area sustainable heritage preservation management plan with the proposal of preservation guidelines for the specific area sustainable preservation in Taiping City. This output where is area and building sustainable heritage preservation plan could help the local authority to determine the suitable preservation for their administrative area.Â Â